Legal Protection of Children Involved in Cases of Fights Between Studentss Based on a Criminological Perspective - Landrawan, I Wayan; Sari Adnyani, Ni Ketut Ni; Agustini, Dewa Ayu Eka Ayu (Universitas Negeri Malang, 2023)
This study aims to analyze the basic principles in the juvenile justice system in Indonesia as well as legal protection for children involved in cases of fights between students. This study uses normative legal research methods with conceptual, legal, and case approaches. The juvenile justice system in Indonesia is based on the principle of parens patriae based on the provisions of Article 6 paragraph (2) of Law Number 4 of 1979 which states that children found guilty of violating the law must be provided with services and care. Legal protection for children involved in cases of fights between students can be categorized into two, namely preventive and repressive legal protection. Preventive legal protection can be done in two ways, namely by conducting socialization and raids to prevent fights between students. Repressive legal protection can be done in three ways, namely by carrying out restorative justice, punishment based on a judge’s decision, or rehabilitation.